1985
DOI: 10.1148/radiology.157.2.4048433
|View full text |Cite
|
Sign up to set email alerts
|

Expanding spectrum of pulmonary disease caused by nontuberculous mycobacteria.

Abstract: The clinical and radiographic features of 35 patients with nontuberculous mycobacterial (NTMB) pulmonary infections were reviewed. Radiographs of half the patients showed the pattern of cavitary upper-lobe infiltrates typical of reactivation tuberculosis; those of the other half had a radiographic pattern characterized by patchy, nodular infiltrates without an upper-lobe prevalence. Approximately half of the latter group showed multiple small cavities resembling those seen in bronchiectasis. These results sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1
2

Year Published

1989
1989
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 0 publications
1
29
1
2
Order By: Relevance
“…It has been reported that the upper lobe cavitary and the nodular bronchiectatic forms are responsible for most NTM infections in immunocompetent patients [19][20][21][22][23][24]. The cavitary form is usually seen in older, white males with underlying chronic pulmonary disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the upper lobe cavitary and the nodular bronchiectatic forms are responsible for most NTM infections in immunocompetent patients [19][20][21][22][23][24]. The cavitary form is usually seen in older, white males with underlying chronic pulmonary disease.…”
Section: Discussionmentioning
confidence: 99%
“…The cavities are usually small and thin walled. The nodular bronchiectatic form is usually seen in middle-aged or older females with no predisposing factors [14,19,25,26]. CT findings of the nodular bronchiectatic form include small centrilobular nodules with bronchiectasis, usually occurring in the same lobe [13,23,24,[27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding radiological findings for pulmonary MAC disease, Albelda et al noted that alveolar infiltration, and nodular, cavitary lesions were characteristic (8). Otherwise, Tanaka et al reported that the transitional pattern of pulmonary MAC disease was initially characterized by subpleural multiple small nodules and secondary bronchial wall thickening and dilatation (9).…”
Section: Discussionmentioning
confidence: 99%
“…In one series,disease was localized to only the right middle lobe on lingula in 20% of patients [5]. In another series, 50% of patients had small, thin-walled structures resembling those seen in bnonchiectasis [2]. Both series used only plain chest radiognaphs for imaging evaluation.…”
Section: Diseasementioning
confidence: 99%